2021
DOI: 10.1001/jamanetworkopen.2021.24502
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Human Papillomavirus Vaccine Safety Concerns and Adverse Event Reporting in the United States

Abstract: Key Points Question Does public sentiment of human papillomavirus (HPV) vaccine safety align with spontaneous HPV vaccine adverse event reporting data? Findings This cross-sectional analysis of the 2015 to 2018 National Immunization Survey indicates a 79.9% increase in the proportion of parents who refused the HPV vaccine for their adolescents due to safety concerns. In contrast, estimates from the national vaccine safety surveillance system found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 43 publications
(112 reference statements)
4
61
0
Order By: Relevance
“…While we did not interview the mothers of participants who reported a lack of maternal support to vaccinate, it is possible that this lack of support was rooted in concerns around the vaccine’s safety. Prior research has cited safety concerns as the primary reason caregivers of adolescents do not initiate the HPV vaccine series [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not interview the mothers of participants who reported a lack of maternal support to vaccinate, it is possible that this lack of support was rooted in concerns around the vaccine’s safety. Prior research has cited safety concerns as the primary reason caregivers of adolescents do not initiate the HPV vaccine series [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study by Cunningham-Erves et al, perceived parent vaccine hesitancy by providers was significantly associated with lower provider confidence in vaccine safety, lower outcome expectations for the discussion and lower self-efficacy (Cunningham-Erves et al, 2019 ). Parental concerns about the safety of the HPV vaccine appear to be increasing – an analysis of NIS-Teen data from 2015 to 2018 found that the proportion of parents citing “Safety Concerns” as the primary reason for not vaccinating their child increased significantly from 13.0% in 2015 to 23.4% in 2018 (Sonawane et al, 2021 ). There is evidence that this increase in parental hesitancy is impacting providers as well.…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%
“…In Japan, the repeated broadcast of adverse events, which are regarded as functional disorders, has discouraged many individuals from getting their daughters vaccinated [ 2 , 5 , 11 ]. In the United States, the HPV vaccination rate has risen to around 50% among vaccine-eligible adolescents, with vaccine hesitancy as a main source of the ongoing problem [ 12 ]. It has been demonstrated that the most frequent reason for hesitancy stems from people’s concerns regarding safety and adverse effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the HPV vaccination rate has risen to around 50% among vaccine-eligible adolescents, with vaccine hesitancy as a main source of the ongoing problem [ 12 ]. It has been demonstrated that the most frequent reason for hesitancy stems from people’s concerns regarding safety and adverse effects [ 12 ]. As social media continues to become a major source for public health information, it has become increasingly difficult to filter out wrong and inaccurate information.…”
Section: Introductionmentioning
confidence: 99%